BUMDesMa KAMPUNG TANI: PEMBERDAYAAN EKONOMI MASYARAKAT BERBASIS AKAD SYARIAH DI KABUPATEN PAMEKASAN - Abd Rohman Al Hadifi; Faridatur Rosyidah; Firman Ardiansyah; Ridan Muhtadi (IQTISADIE: Journal of Islamic Banking and Shariah Economy, 2021)
This study aims to provide a conceptual model regarding the optimization and transformation of BUMDes into BUMDesMa through the OVOP Concept approach which is expected to provide a constructive solution in increasing the economic potential of the Pamekasan community as a farming village. In addition, in order to create a halal lifestyle climate, all BUMDes activities are based on sharia contracts. This study uses descriptive qualitative methods with secondary data collection methods obtained from literature and documentaries that have been processed. While the data analysis technique starts from editing, organizing and finding. The results showed that the optimization of the performance of BUMDes has a wider scope, not only applying the concept of one village one product, but also cooperating with several villages that have the same potential to produce a superior commodity that is more leverage so that an innovation called "BUMDesMa Kampung Tani" appears where there are optimization efforts by forming a community that leads to community economic empowerment, starting from the community of raw material producers, creative and innovative, marketing, and waste management. Pamekasan Regency has good potential because the community can establish cooperation starting from capital, raw material production, management, marketing, to the handling of agricultural waste generated. Keywords: BUMDesMa Kampung Tani, OVOP concept, economic empowerment, sharia contract